VD_FINDINFO Pron / 2012 / 81 vom 12. April 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, PREUVE À FUTUR, MESURE PRÉPROVISIONNELLE, DOMMAGE IRRÉPARABLE | 158 al. 2 CPC (CH), 265 CPC (CH)